2018
DOI: 10.5152/kd.2018.24
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antiretroviral Therapy Regimens in Terms of Virological Response, Immunological Response and Adverse Effects in Treatment-Naive HIV-Positive Patients

Abstract: Objective: In this study, we aimed to determine the demographic and clinical characteristics of HIV-positive patients seen in our faculty; and to put forward the differences in virological response, immunological response and adverse effects of administered antiretroviral therapy (ART) regimens in these patients. Methods: Medical records of 175 HIV-positive patients over 18 years old followed between 2003 and 2015 and have not been treated before, and regularly monitored for a minimum of six months from the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(19 reference statements)
1
1
0
1
Order By: Relevance
“…This trend might be explained by the reduction in pill count with NNRTIbased regimens and higher adherence to the treatment. In a study from Turkey, the authors reported good adherence to PI-based regimens with advanced stage of the disease and fewer adverse effects of PI-based regimens compared with NRTI-based regimens even with lower pill counts (19). In the subgroup analyses of the NRTI-based regimen group in our study, it is notable that patients were not in advanced CDC stages of the disease and had a higher baseline CD4+ cell count.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…This trend might be explained by the reduction in pill count with NNRTIbased regimens and higher adherence to the treatment. In a study from Turkey, the authors reported good adherence to PI-based regimens with advanced stage of the disease and fewer adverse effects of PI-based regimens compared with NRTI-based regimens even with lower pill counts (19). In the subgroup analyses of the NRTI-based regimen group in our study, it is notable that patients were not in advanced CDC stages of the disease and had a higher baseline CD4+ cell count.…”
Section: Discussionsupporting
confidence: 44%
“…In another study that compared treatment regimens using VF and IF, in which TDF FTC was the backbone and LPV r or EFV was the 3rd agent, the authors concluded that the regimen that included LPV r was more successful immunologically. In this study, the success of certain treatment regimens, adherence to treatment, and adverse effects were assessed rather than factors influencing treatment success (19). Therefore, to the best of our knowledge, our study is the first in Turkey to assess treatment success with regard to probable risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Tedavi değişikliği sonrası izlemde kullanılacak parametreler kılavuzlarda benzerdir (2)(3). Bununla birlikte, tedavi yanıtının ve yan etkilerin yakın takibi gerekmektedir (4). Literatürde tedavi değişikliği sonrası tedavi yanıtı, yan etki ve uzun dönem takibi açısından sınırlı sayıda gerçek yaşam verisi bulunmaktadır.…”
Section: Introductionunclassified